2002
DOI: 10.1253/circj.66.525
|View full text |Cite
|
Sign up to set email alerts
|

Huge Saccular Aneurysm in a Coronary-Pulmonary Fistula Fed by the Left and Right Coronary Arteries.

Abstract: ecause a communication between the coronary arteries and the cardiac chamber or the pulmonary trunk is not a common anomaly, 1 the formation of an aneurysm in this communication vessel is clinically few. [2][3][4] We report an adult case of a huge aneurysm that was fed by both the left anterior descending and the right coronary artery draining anomalously into the main pulmonary artery. Case ReportA 62-year-old woman was referred to hospital because of an abnormal mediastinal shadow on chest roentgenogram. She… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 9 publications
1
16
0
Order By: Relevance
“…Approximately 50%, 42% and 5% of CAF arise from the RCA, the LAD and both vessels, respectively. The most common drainage sites are low-pressure structures as: the right ventricle (41%), right atrium (26%), pulmonary artery (17%), coronary sinus (7%), left atrium (5%), left ventricle (3%) and the superior vena cava (1%), respectively 1 2. Most fistulas are single communications, but multiple fistulas and fistulas associated with fusiform or saccular aneurysms have been reported 3.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 50%, 42% and 5% of CAF arise from the RCA, the LAD and both vessels, respectively. The most common drainage sites are low-pressure structures as: the right ventricle (41%), right atrium (26%), pulmonary artery (17%), coronary sinus (7%), left atrium (5%), left ventricle (3%) and the superior vena cava (1%), respectively 1 2. Most fistulas are single communications, but multiple fistulas and fistulas associated with fusiform or saccular aneurysms have been reported 3.…”
Section: Discussionmentioning
confidence: 99%
“…There is a previous report of giant aneurysm in coronary -pulmonary fistula with cystic medial change [2]. By contrast, some reported that the wall of saccular aneurysms had calcified change [3 -5].…”
Section: Discussionmentioning
confidence: 99%
“…Saccular aneurysm in coronary -pulmonary fistula is extremely rare [1][2][3]. There is a previous report of giant aneurysm in coronary -pulmonary fistula with cystic medial change [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although a coronary artery aneurysm associated with a fistula may result secondarily from atherosclerotic changes or traumatic injury to the fistula, it is even more rare than coronary artery fistulas. 2,3) The clinicopathologic characteristics of a coronary artery fistula concomitant with a coronary artery aneurysm are poorly understood because of their rarity.…”
Section: Introductionmentioning
confidence: 99%